SCAI/AATS/ACC/STS operator and institutional requirements for transcatheter valve repair and replacement, Part III: Pulmonic valve. Issue 1 (24th March 2015) - Hijazi, Ziyad M.; Ruiz, Carlos E.; Zahn, Evan; Ringel, Richard; Aldea, Gabriel S.; Bacha, Emile A.; Bavaria, Joseph; Bolman, R. Morton; Cameron, Duke E.; Dean, Larry S.; Feldman, Ted; Fullerton, David; et al.
PREAMBLE With the evolution of transcatheter valve replacement, an important opportunity has arisen for cardiologists and surgeons to collaborate in identifying the criteria for performing these procedures. Therefore, The Society for Cardiovascular Angiography and Interventions (SCAI), American Association for Thoracic Surgery (AATS), American College of Cardiology (ACC), and The Society of Thoracic Surgeons (STS) have partnered to provide recommendations for institutions to assess their potential for instituting and/or maintaining a transcatheter valve program. This article concerns transcatheter pulmonic valve replacement (tPVR). tPVR procedures are in their infancy with few reports available on which to base an expert consensus statement. Therefore, many of these recommendations are based on expert consensus and the few reports available. As the procedures evolve, technology advances, experience grows, and more data accumulate, there will certainly be a need to update this consensus statement. The writing committee and participating societies believe that the recommendations in this report serve as appropriate requisites. In some ways, these recommendations apply to institutions more than to individuals. There is a strong consensus that these new valve therapies are best performed using a Heart Team approach; thus, these credentialing criteria should be applied at the institutional level. Partnering societies used the ACC's policy on relationships with industry (RWI) and other entities to author this document (http://www.acc.org/guidelines/about-guidelines-and-clinical-documents). To avoid actual, potential, or perceived conflicts of interest due to industry relationships or personal interests, all members of the writing committee, as well as peer reviewers of the document, were asked to disclose all current healthcare‐related relationships including those existing 12 months before the initiation of the writing effort. A committee of interventional cardiologists and surgeons was formed to include a majority of members with no relevant RWI and to be led by an interventional cardiology cochair and a surgical cochair with no relevant RWI. Authors with relevant RWI were not permitted to draft or vote on text or recommendations pertaining to their RWI. RWI were reviewed on all conference calls and updated as changes occurred. Author and peer reviewer RWI pertinent to this document are disclosed in the Appendices. In addition, to ensure complete transparency, authors' comprehensive disclosure information (including RWI not pertinent to this document) is available in Appendix AII. The work of the writing committee was supported exclusively by the partnering societies without commercial support. SCAI, AATS, ACC, and STS believe that adherence to these recommendations will maximize the chances that these therapies will become a successful part of the armamentarium for treating valvular heart disease in the United States. In addition, these recommendations will hopefully facilitate optimum quality during the delivery of this therapy, which will be important to the development and successful implementation of future, less invasive approaches to structural heart disease.